Impact of pre-pregnancy body mass index on preeclampsia - Mao, Jing; Sun, Hanxiang; Shen, Qinxin; Zou, Chang; Yang, Yuanyuan; Du, Qiaoling (Frontiers in Medicine, 2025)
BackgroundIt remains unclear how pre-pregnancy body mass index (BMI) affects preeclampsia in the Chinese population, primarily due to insufficient large-scale research on this topic.ObjectiveThe study aimed to determine the relationship between pre-pregnancy BMI and (severe) preeclampsia in the Chinese population, providing a detailed description of the findings.MethodsThe retrospective study included a total of 75,773 pregnant women registered between 2016 and 2020. These participants were categorized into four groups based on their pre-pregnancy BMI: underweight (BMI < 18.5 kg/m2), normal weight (BMI 18.5–<24 kg/m2), overweight (BMI 24–<28 kg/m2), and obese (BMI ≥ 28 kg/m2). The relationship between risks of preeclampsia or severe preeclampsia and pre-pregnancy BMI were further explored, with an evaluation of potential modification by maternal age.ResultsA lower risk of developing preeclampsia was observed in the underweight population, with an OR of 0.604 (95%CI, 0.507–0.719). In contrast, women who were overweight or obese during the pre-pregnancy period demonstrated a significantly higher risk of preeclampsia, with ORs of 2.211 (95%CI, 1.967–2.486) and 3.662 (95%CI, 3.026–4.431), respectively. After adjusting for confounding factors, the elevated risk of preeclampsia persisted, showing ORs of 2.152(95%CI, 1.911–2.425) for the overweight population and 3.493 (95%CI, 2.874–4.245) for those who were obese, while the risk for underweight women remained lower, with an OR of 0.609(95%CI, 0.511–0.727). For severe preeclampsia, the risk was also higher in the overweight and obese participants after adjusting for confounders, demonstrating ORs of 1.652(95%CI, 1.364–2.001) and 2.762(95%CI, 2.014–3.788), respectively. The underweight population exhibited a lower risk of severe preeclampsia, with an OR of 0.720(95%CI, 0.565–0.919). In addition, these risks were not significantly associated with maternal age.ConclusionRegardless of adjustment for confounders, underweight women demonstrated a lower risk of preeclampsia, whereas the overweight/obese population exhibited a higher occurrence of both preeclampsia and severe preeclampsia. These associations were not influenced by maternal age.